The Arab Spring Through the Lenses of Ibn Khaldun - Souad Adnane (İbn Haldun Çalışmaları Dergisi, 2017)
The “Arab state” has also gone through phases, the five stages of the state life cycle as described by Ibn Khaldun, and it has also known many transformations. How can we analyze these political and social transformations and how are they interacting with each other from a Khaldunian perspective? How can we understand this current particular phase between the fall of the “Arab state”, as we’ve known it until now, and the rise of a “new” one in the light of Ibn Khaldun’s theory? A new phase characterized by ethnic conflicts that have taken a more apparent and obvious form in the aftermath of the Arab Spring. What are possible avenues to get rid of despotism and violence? The present paper is an attempt to answer these questions applying Ibn Khaldun’s theoretical framework to the current events and context of the Arab world.